2019
DOI: 10.4236/jss.2019.76007
|View full text |Cite
|
Sign up to set email alerts
|

Reading Motivation vis-s-vis Academic Performance

Abstract: Abundant literature can be sourced out from different authorities about reading motivation, yet little work can be traced between this component and the academic achievement. Hypothesizing that motivation has a significant relationship to success, this study attempted to investigate such a particular connection. The researchers used a modified version of the Motivation for Reading Questionnaire (MRQ) administered to 82 Grade III pupils, of which the first half were required to answer the questions for pilot te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
7
2
0
Order By: Relevance
“…While the statement "The learners do not like if there are too many people in the story" has the lowest mean of 2.23, it is interpreted as moderately motivated, which means that the respondents still have less interest in reading. This finding is similar to the study of Alvarado et al [27], whose findings, according to them, mirror the present condition of the entire Philippine society. Based on their study, learners do not like to read out loud in class for fear of being ridiculed or made fun of, especially when they commit mistakes in pronouncing words or phrases.…”
Section: The Level Of Reading Motivation Of the Respondentssupporting
confidence: 92%
See 2 more Smart Citations
“…While the statement "The learners do not like if there are too many people in the story" has the lowest mean of 2.23, it is interpreted as moderately motivated, which means that the respondents still have less interest in reading. This finding is similar to the study of Alvarado et al [27], whose findings, according to them, mirror the present condition of the entire Philippine society. Based on their study, learners do not like to read out loud in class for fear of being ridiculed or made fun of, especially when they commit mistakes in pronouncing words or phrases.…”
Section: The Level Of Reading Motivation Of the Respondentssupporting
confidence: 92%
“…This study supports the claim of Alvarado et al [27], who revealed that the learners are more than willing to tell their families about the books, textbooks, magazines, articles, and other items they read. The social motivation for reading relates to the interpersonal and community activities involving the learners.…”
Section: The Level Of Reading Motivation Of the Respondentssupporting
confidence: 90%
See 1 more Smart Citation
“…Although the participants' reading motivation indicators were positively received, they also showed hesitation to read confidently in front of their classmates and teachers [39]. In addition, students' perspectives and behavior show many factors affecting their attitude toward school.…”
Section: Relationship Between Reading Motivation and Student Attitude...mentioning
confidence: 95%
“…2021), and (2) a questionnaire for taking the students responses to the use of crosswords, which was administered by the help of google form, you may check the link of the questionnaire here, the questionnaire had also been validated and had been checked its reliability and you may check the validity and reliability status here (sheet 6). The questionnaire was composed of 10 questions due on the theory of reading motivation (to see the impact of crosswords as a reading comprehension assessment on the students reading motivation (Al Seghayer, 2013;Alhamdu, 2016;Alvarado & Adriatico, 2019;Baba Öztürk & Aydogmus, 2021;Baki, 2020;Davis et al, 2018;Dukpa & Dhendup, 2021;Huang & Reynolds, 2022;Jones, 2020;Rohmani, 2022;Vera Valencia, 2017;Wigfield et al, 2016)), moreover, the questionnaire used the Linkert scale of disagree, quite agree, agree, and strongly agree. The The data was taken in two procedures (1) the students were taught by applying the crosswords in the coursebooks and (2) the questionnaire was administered after the learning process.…”
Section: Methodsmentioning
confidence: 99%